The Role of Poetry in Encouraging Students to Speak in an English Conversation Club - Aftinia, Fitria (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This study aimed to know the students' activities during learning by using poetry and find out the students' perception of using poetry in learning English in the English Conversation Club. To conduct the study, twenty students who joined the English Conversation Club in a private senior high school in Surabaya, Indonesia, participated. The data were obtained from observation and a questionnaire. The result of the observation was explained descriptively, and the questionnaire result was calculated in percentages and categorized. The results showed that the students followed the instruction but had difficulty understanding the content of the poetry because of the figurative language. Besides, students' perception of using poetry is mostly positive, especially for improving their speaking skills. Using poetry as a literary text in English Language Teaching (ELT) could be an alternative way to introduce literature and encourage students to speak.